2023
DOI: 10.1159/000530129
|View full text |Cite
|
Sign up to set email alerts
|

Essential Fatty Acid Supplementation and Early Inflammation in Preterm Infants: Secondary Analysis of a Randomized Clinical Trial

Abstract: <b><i>Introduction:</i></b> Postnatal inflammation is associated with increased mortality and adverse outcomes in preterm infants. The essential fatty acids arachidonic acid (ARA) and docosahexaenoic acid (DHA) are precursors of lipid mediators with a key role in resolving inflammation. Our aim was to investigate the effect of ARA and DHA supplementation on systemic inflammation in very preterm infants and to identify clinical factors associated with early inflammation. <b><i&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…In this study, enteral ARA and DHA supplementation during neonatal hospitalization in infants with GA < 29 weeks did not lead to improved lung function at 3 months CA. Despite the positive effect on early inflammation and short‐term lung function previously reported, 6,7 we did not find any differences in t PTEF / t E ratio or tidal volumes per kilo between the study groups. Twenty‐four percent of the study participants with an awake TFV assessment had a t PTEF / t E ratio ≤ 0.25, a cut‐off regarded to represent impaired lung function during infancy 13 .…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…In this study, enteral ARA and DHA supplementation during neonatal hospitalization in infants with GA < 29 weeks did not lead to improved lung function at 3 months CA. Despite the positive effect on early inflammation and short‐term lung function previously reported, 6,7 we did not find any differences in t PTEF / t E ratio or tidal volumes per kilo between the study groups. Twenty‐four percent of the study participants with an awake TFV assessment had a t PTEF / t E ratio ≤ 0.25, a cut‐off regarded to represent impaired lung function during infancy 13 .…”
Section: Discussioncontrasting
confidence: 94%
“…Despite the anti‐inflammatory properties of DHA, there are concerns that DHA supplementation may increase the risk of BPD 5 . However, in a randomized controlled trial (ImNuT) we recently reported that infants with GA < 29 weeks had less systemic inflammation and fewer days with respiratory support after enteral ARA and DHA supplementation during neonatal hospitalization 6,7 . The effect of a balanced supply of both ARA and DHA on lung function development is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Despite modulating markers of inflammation (i.e. lowering interleukine-6), supplementation with ARA and DHA did not alter the risk of BPD or other major neonatal morbidities [48 ▪ ,49 ▪ ]. There was also no difference in lung function at 3 months corrected age [50].…”
Section: Long Chain-polyunsaturated Fatty Acids Functional Role and S...mentioning
confidence: 93%
“…7 A RCT has demonstrated that enhanced supplementation with ARA 100 mg per kg and DHA 50 mg per kg (ARA/DHA = 2 : 1) may modulate inflammation in very preterm infants. 96 So far, studies have concentrated on the beneficial effects of various ARA to DHA ratios on infant development, specifically focusing on cognitive and immune development (Table 4).…”
Section: Functions Of Different Ratios Of Ara and Dhamentioning
confidence: 99%